Implementasi Gamifikasi dalam Pendidikan Biologi (Studi Literatur Sistematis Tahun 2021–2025) - Saidah, Nurul; Jalil, Muhammad (Symbiotic: Journal of Biological Education and Science, 2025)
Learning innovation is indispensable in the world of education. Challenges in biology learning are lack of student focus, low learning motivation, and student learning outcomes are still less than average. The purpose of this study is so that biology learning has development in learning methods. The benefits of this research are to develop an academic understanding of the impact of gamification on biology learning with evidence of existing journal articles. The type of research used is systematic literature review, which is a method used to analyze, review and explain existing research to answer the formulation of the problem to be researched. The selected journal article must meet the criteria, namely the topic of the application of gamification in biology learning or gamification-based learning media in biology learning, has a time span of 2021 to 2025, the selected journal articles are only those published on google scholar with an index of sinta 2 to sinta 5. The articles reviewed totaled 12 that were relevant to the research. The results of this study show that gamification can significantly increase activeness, learning motivation, student focus, and learning outcomes. Gamification in biology learning can improve quality learning goals.The results of this study show that gamification can significantly increase student activity, learning motivation, focus, and learning outcomes. Gamification in biology learning can improve quality learning objectives.